Dialogue in the Plowing Ritual in Sergei Yesenin’s Story Yar and its Mythological Connotations - Rakhno, Konstantin (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
One of the most striking episodes in Sergei Yesenin’s story Yar (1915) is the description of the folk ritual of ploughing a village against an anthrax epizootic. It is ethnographically accurate, based on the personal impressions of the poet as an eyewitness, and contains a number of important details that complement the records of the 19th – early 20th centuries. The ploughing that Yesenin saw in his native village belongs to the so-called occasional rituals, which are only resorted to during crises, such as mass illnesses of people and deaths of livestock, which were thought to mean failure in the world order. To stop the epidemic a balance had to be restored between the “human” and the “non-human”. Accordingly, the epidemic was thought of as evidence that the balance had been disrupted, and that the border separating people from the other world had weakened. The rite of ploughing was intended to renew it on the real and symbolic levels. Eleven naked innocent girls, led by a blindfolded married woman, circled the village with chants. They became participants in primordial creation. According to Yesenin, during the ritual walk they could kill any person they met who was deemed to personify the disease. Moreover, the dialogue between the blindfolded woman and the participants in the ritual reproduced ritual blindness, which made it possible to see another existence, and invoked the corresponding mythological characters such as Gogol’s Viy.